The Role of the Iraqi Tax System in Addressing Economic Crises - Al-Sharqawi, Ibrahim; Hamza, Marwa (Journal of Legal Sciences, 2025)
During times of economic crises, individuals, particularly those with lower incomes, seek guidance as well as social and economic protection from the established political structure. This requires a focused and coordinated effort by governmental institutions to tackle the consecutive economic crises that the country is experiencing. Taxes serve as a significant tool for the state to exert influence over economic activity and play a vital part in addressing economic crises. This position entails the attainment of economic stability as a primary objective, in addition to its social and political goals. This is achieved by generating targeted tax revenues and taking into account the sectors that are impacted during times of crisis. The tax system is crucial in the aftermath of a crisis as it helps to tackle the economic and social consequences of the crisis. This includes dealing with reduced tax revenues, which have a long-lasting impact, contributing to the state's budget deficit, and providing support to the groups affected by the crisis.